Correction: Large-sized graphene oxide synergistically enhances parenchymal hepatocyte IL-6 expression monitored by dynamic imaging. Issue 16 (22nd April 2020) - Zhang, Yulong; Ma, Cong; Wang, Zhengjun; Zhou, Qianqian; Sun, Sujing; Ma, Ping; Lv, Liping; Jiang, Xinquan; Wang, Xiaohui; Zhan, Linsheng
Abstract : Correction for 'Large-sized graphene oxide synergistically enhances parenchymal hepatocyte IL-6 expression monitored by dynamic imaging' by Yulong Zhang et al., Nanoscale, 2020, DOI: ; 10.1039/C9NR10713D .